The current epidemic of obesity: causes, mechanisms, excessive food absorption physiology: Systematic review - Kuat Oshakbayev; Bibazhar Dukenbayeva (National Scientific Medical Center, 2016)
Purpose: To discuss and present the most likely cause of a broad manifestation of obesity and chronic non-communicable diseases among population in recent years, in conjunction with some of the issues nutrition physiology, absorption and energy balance. Methods: A systematic review with the elements of inductive-deductive analysis using databases of Thomson Reuters (WebOfScience), SpringerLink, Elsevier (Science Direct), PubMed (MedLine), Cochrane Library. Results: An ordinary person consumes food as more as than is necessary to his body, which has a negative impact on his health and quality of life. A malaise state during more than 12-15 hours without food intake due to the occurrence of metabolic intoxication within endogenous lipolysis. The ration food of a common person includes a lot of stimulating appetite supplements, as well as a wide variety, availability, and cooking products. The body spends own energy/substances resources for food digestive process. The body losses own energy regularly, if there is no subsequent absorption and transport of nutrients to functional cells. Obese impacts people in all over the world regardless of the economy or political systems. Obesity is a major factor increasing the risk of chronic non-communicable diseases, premature death, reduces a quality of life in people. Conclusion: For common persons has been created a great temptation for receiving excess food. The instincts and habits saving people still lead to overweight and obesity. Eaten calories are not always used and absorbed by the body. The majority of a population is not enough behavior skills at the presence of excess food. Ones should not blindly follow the conditioned reflex eating with his continuing accessibility. Necessary to change the level of consumption (food habits) with an increase in accessibility of food with a principles development of adequate physiologic nutrition.